2009
DOI: 10.1007/s11274-009-0255-4
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds produced by Saccharomyces cerevisiae inhibit the in vitro development of Guignardia citricarpa, the causal agent of citrus black spot

Abstract: Due to the low chemical control effectiveness of citrus black spot, caused by the fungus Guignardia citricarpa at postharvest, and to the search for alternative control methods, this study aimed to evaluate the in vitro effect of volatile organic compounds (VOCs), produced by yeast Saccharomyces cerevisiae, on G. citricarpa. It was observed that the yeast strains evaluated acted as antagonists by VOC production, whose maximum inhibitory capacity was as high as 87.2%. The presence of fermentable carbon sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 31 publications
3
62
0
2
Order By: Relevance
“…However, neither ethanol nor bisabolol were tested for toxicity to phytonematodes. The four VOCs produced by E. nigrum (PD8) and S. commune (PD29) (ethanol, 2-methyl-propanol, 3-methyl-butanol, and 2-methyl-butanol) are typical fungal compounds that have been detected in other studies to evaluate the effect of VOCs on nematodes (Fialho et al, 2010;Grimme et al, 2007). However, the compounds methanethiol, methylthioacetate, 3-methyl-butanol acetate and 2-methyl-butanol acetate were produced only by S. commune (PD29) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither ethanol nor bisabolol were tested for toxicity to phytonematodes. The four VOCs produced by E. nigrum (PD8) and S. commune (PD29) (ethanol, 2-methyl-propanol, 3-methyl-butanol, and 2-methyl-butanol) are typical fungal compounds that have been detected in other studies to evaluate the effect of VOCs on nematodes (Fialho et al, 2010;Grimme et al, 2007). However, the compounds methanethiol, methylthioacetate, 3-methyl-butanol acetate and 2-methyl-butanol acetate were produced only by S. commune (PD29) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Grimme et al (2007) used an artificial mixture of volatiles produced by the fungus M. albus, including 3-methyl-1-butanol, 3-methyl-1-butanol acetate and some esters, and found that this mixture reduced the number of root galls by M. incognita in tomato plants in vivo. Fialho et al (2010) reported that VOCs consisting of alcohols are mainly responsible for the bioactivity of Saccharomyces cerevisiae against the fungus Guignardia citricicarpa. According to the authors, an artificial mixture of VOCs with the compounds 3-methyl-1-butanol and 2-methyl-1-butanol was able to fully suppress the development of G. citricicarpa.…”
Section: Discussionmentioning
confidence: 99%
“…As volatile antifungal substance-producing yeast, P. anomala and Saccharomyces cerevisiae CR-1 were isolated during processing of Caffea arabica (Masoud et al, 2005) and ethanol fermentation (Fialho, Toffano, Pedroso, Augusto, & Pascholati, 2010), respectively. A major volatility antifungal substance generated by P. anomala is phenethyl acetate.…”
Section: Discussionmentioning
confidence: 99%
“…Yeasts generate volatile antifungal substances, such as phenethyl acetate, ethyl acetate, isobutyl acetate, isoamyl acetate, isoamyl alcohol, phenethyl alcohol, and 2-pentanone (Bruce, Verrall, Hackett, & Wheatley, 2004;Fialho et al, 2010;Masoud et al, 2005). C. maltosa NP9 also generated seven substances in the gas-phase when grown on the YPD plate (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have shown the inhibition potential of increasing doses of an artificial mixture of VOCs isolated from S. cerevisiae against the mycelial growth of G. citricarpa, with this inhibition reaching up to 88% (Fialho et al, 2010).…”
Section: Discussionmentioning
confidence: 99%